2022
DOI: 10.1088/1741-4326/ac486b
|View full text |Cite
|
Sign up to set email alerts
|

Simulation prediction of micro-instability transition and associated particle transport in tokamak plasmas

Abstract: Two reduced simulation approaches are exploited to predict the parametric boundary of dominant instability regime with global effects and the characteristics of corresponding turbulent particle fluxes in tokamak plasmas. One is usual numerical simulation of coexisting ion temperature gradient (ITG) mode and trapped electron mode (TEM) turbulence employing an extended fluid code (ExFC) based on the so-called Landau-Fluid model including the trapped electron dynamics. Here the density gradient (i.e. R/Ln) driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…2021 b ; Li et al. 2022; Rodriguez-Fernandez et al. 2022 b ) have found that the total particle flux can be a sensitive function of the mix of ITG and TEM turbulence present, and gyrokinetic simulations have shown that nonlinear couplings between these modes are possible (Merz & Jenko 2010).…”
Section: Core Transportmentioning
confidence: 99%
“…2021 b ; Li et al. 2022; Rodriguez-Fernandez et al. 2022 b ) have found that the total particle flux can be a sensitive function of the mix of ITG and TEM turbulence present, and gyrokinetic simulations have shown that nonlinear couplings between these modes are possible (Merz & Jenko 2010).…”
Section: Core Transportmentioning
confidence: 99%
“…Jonas et al successfully apply AI to automatically control a variety of plasma boundary shapes on the TCV device [17] . In numerical simulations, Zhao et al accomplished quick prediction of beta limits in HL-2M device via AI, with an accuracy rate being as high as 95% [18] . Li et al build a surrogate model through AI to predict the transition of micro-instability in fusion devices [19] .…”
Section: The Rise Of Artificial Intelligent (Ai) Trendsmentioning
confidence: 99%
“…Further details of the equations and the simulation code were shown in our recent work. [35,36] The ITG and TEM instabilities are involved in this multi-mode model, including plasma density 𝑛e, electron temperature 𝑇e, vorticity 𝛺, parallel ion velocity 𝜐 ‖ and ion temperature 𝑇i:…”
mentioning
confidence: 99%